Solar cycle response and long‐term trends in the mesospheric metal layers. Issue 7 (27th July 2016) - Dawkins, E. C. M.; Plane, J. M. C.; Chipperfield, M. P.; Feng, W.; Marsh, D. R.; Höffner, J.; Janches, D.
Abstract: The meteoric metal layers (Na, Fe, and K)—which form as a result of the ablation of incoming meteors—act as unique tracers for chemical and dynamical processes that occur within the upper mesosphere/lower thermosphere region. In this work, we examine whether these metal layers are sensitive indicators of decadal long‐term changes within the upper atmosphere. Output from a whole‐atmosphere climate model is used to assess the response of the Na, K, and Fe layers across a 50 year period (1955–2005). At short timescales, the K layer has previously been shown to exhibit a very different seasonal behavior compared to the other metals. Here we show that this unusual behavior is also exhibited at longer timescales (both the ~11 year solar cycle and 50 year periods), where K displays a much more pronounced response to atmospheric temperature changes than either Na or Fe. The contrasting solar cycle behavior of the K and Na layers predicted by the model is confirmed using satellite and lidar observations for the period 2004–2013. Key Points: First study of response of modeled metal layers to changing atmosphere K is the only metal to exhibit pronounced response to atmospheric changes at 11 year solar cycle and longer‐term (50 year) timescales K layer may be good candidate as a sensitive indicator of long‐term changes in the mesosphere/lower thermosphere region